Analysis Of Stakeholder Contributions To The Development Of Madrasah Quality Madrasah In MAN Asahan - Siti Syevila; Makmur Syukri (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
This article examines madrasas that are significant in supporting the achievement of national education goals. Efforts to improve the quality of madrasas as superior and quality educational institutions, always innovate and take concrete steps in developing the vision and mission of madrasas and collaborate with all madrasa stakeholders. Therefore, the role of stakeholders is very important in formulating policies that aim to improve the quality of education in educational institutions. The study was conducted using a qualitative method with in-depth interview techniques on madrasa stakeholders. The qualitative approach is used to describe the reality of the events studied so as to obtain objective data. The results of this study indicate that each stakeholder has a complementary role in improving the quality of education at MAN Asahan. Therefore, participation from various stakeholders is very important to improve madrasas. Stakeholders are also able to mobilize all elements of the madrasa to realize a quality vision and mission in the madrasa. It can be concluded that the role of stakeholders in building madrasas at MAN Asahan must involve all stakeholders to build quality madrasas with positive synergy between the head of the madrasa, teachers, students, and parents who together form an effective support system for the progress of madrasas at MAN Asahan.